A Bibliometric Review of Sustainable Facility Layout Research: Trends, Optimization Approaches, and Future Directions - Lely Herlina; Muhammad Adha Ilhami; Yusraini Muharni; Evi Febianti; Ade Irman Saeful Mutaqin; Kulsum Kulsum; Anting Wulandari (Universitas Sultan Ageng Tirtayasa, 2026)
Facility layout design has become increasingly connected with sustainability-oriented manufacturing because layout decisions influence material handling, energy efficiency, environmental impact, and human factors. This study conducts a bibliometric analysis and systematic literature review to map the development of Sustainable Facility Layout research. Publications were retrieved from Scopus using the keywords “Sustainable Facility Layout,” “Sustainable Layout,” and “Sustainable Systematic Layout.” From 24 initial records, 14 relevant articles were selected and analyzed using VOSviewer version 1.6.20 with the Association Strength normalization method. The keyword co-occurrence analysis identified 205 keywords, which were filtered into 16 relevant keywords and five thematic clusters. The results show that current research is dominated by energy efficiency, environmental impact, sustainability, and layout optimization, while machine learning, Genetic Algorithm, and multi-objective optimization are emerging as intelligent optimization approaches. The findings also indicate that economic and social effects remain less explored than environmental and operational dimensions. This review contributes by presenting an integrated taxonomy of Sustainable Facility Layout studies and identifying future research directions related to AI-driven optimization, digital twin-based layout systems, carbon-aware facility planning, and human-centric sustainable manufacturing.